1984
DOI: 10.1111/j.1469-8749.1984.tb04459.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Spatial Defect in a Child with Septo‐optic Dysplasia

Abstract: A blind girl with septo-optic dysplasia was compared with a blind, age-matched control on three spatial tests. Previous observations had suggested a specific spatial learning disorder. Results of the tests showed good verbal intelligence but severe impairment of topographical orientation, route-learning and kinaesthetic memory. It is argued that these dysfunctions were a direct consequence of the malformation syndrome, and could not be accounted for by factors such as sex or congenital blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Our understanding of the aetiology of PHD has advanced considerably in recent years, and a small but expanding number of genes are known to be important in the development of midline structures. Studies of a blind child with septo-optic dysplasia identified a specific spatial learning defect when compared to a blind control child, 10 and our observations could be linked to the abnormal development of midline structures. Abnormalities of brain development in PHD can also include structures other than those in the midline, and impaired perceptual organisational skills may be a manifestation of impaired visual processing in an abnormally developed brain.…”
Section: Discussionsupporting
confidence: 58%
“…Our understanding of the aetiology of PHD has advanced considerably in recent years, and a small but expanding number of genes are known to be important in the development of midline structures. Studies of a blind child with septo-optic dysplasia identified a specific spatial learning defect when compared to a blind control child, 10 and our observations could be linked to the abnormal development of midline structures. Abnormalities of brain development in PHD can also include structures other than those in the midline, and impaired perceptual organisational skills may be a manifestation of impaired visual processing in an abnormally developed brain.…”
Section: Discussionsupporting
confidence: 58%
“…Subsequent findings confirmed the high prevalence [31], including findings from a prospective study [8]. Developmental delay ranges from isolated focal defects to global delay [88, 89]. Using a standardized neuropsychological instrument and longitudinal follow-up until 5 years of age, developmental delays were identified in 71 % of children with ONH.…”
Section: Neuropsychological Outcomesmentioning
confidence: 71%
“…[26][27][28][29] Overall delay occurred in 71% of our subjects, with motor delays being the most common (75%) and communication delays the least common (44%). Brodsky and Glasier 8 previously reported a positive association between delay and any neuroradiographic abnormality in a retrospective study of patients with severe cases of ONH.…”
Section: Discussionmentioning
confidence: 99%